2006
DOI: 10.1177/0734282906290594
|View full text |Cite
|
Sign up to set email alerts
|

Teacher and Classroom Characteristics Associated With Teachers’ Ratings of Prekindergartners’ Relationships and Behaviors

Abstract: Teachers’ ratings of children’s competencies may in part reflect characteristics and perspectives of teachers who assigned the ratings, which compromises their validity as a measure of child attributes. The purposes of this study were to use multilevel modeling to (a) estimate between-rater variance in teachers’ ratings of children’s social behaviors and relationships with teachers and (b) examine characteristics of teachers and classrooms associated with teachers’ perceptions of these social competencies. Rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
190
6
10

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 248 publications
(232 citation statements)
references
References 24 publications
16
190
6
10
Order By: Relevance
“…Similarly, the percentage of teacher-student relationships in the classroom judged as negative by the teacher has been found to be associated with teacher reports of stress and negative emotions (Yoon 2002). In contrast, Mashburn et al (2006) found that it was closeness, and not conflict, that was positively related to teachers' efficacy beliefs regarding management of difficult child behavior in a sample of pre-kindergarten teachers. They did not find linkages between teacher-student relationship quality and teacher-reported depression.…”
Section: The Influence Of Teacher-student Relationships On Teacher Wementioning
confidence: 39%
See 1 more Smart Citation
“…Similarly, the percentage of teacher-student relationships in the classroom judged as negative by the teacher has been found to be associated with teacher reports of stress and negative emotions (Yoon 2002). In contrast, Mashburn et al (2006) found that it was closeness, and not conflict, that was positively related to teachers' efficacy beliefs regarding management of difficult child behavior in a sample of pre-kindergarten teachers. They did not find linkages between teacher-student relationship quality and teacher-reported depression.…”
Section: The Influence Of Teacher-student Relationships On Teacher Wementioning
confidence: 39%
“…However, there may be just a few students with more severe behavior problems who have a relatively strong influence on discipline issues and levels of stress experienced by teachers. Accordingly, there is much differentiation within teachers in their perceptions of behavioral problems and relational conflict (e.g., Mashburn et al 2006). Research into teaching stress indicates that problem behaviors do not necessarily lead to stress.…”
Section: Can Teachers' Mental Relationship Models Explain the Associamentioning
confidence: 99%
“…More recently, researchers have begun to show how personal characteristics of teachers can influence their assessments of the teacher-child relationship (Hamre, Pianta, Downer, & Mashburn, 2008;Kesner, 2000;Mashburn, Hamre, Downer, & Pianta, 2006). The present study aims to expand upon this line of research by examining how teachers' reports of their relationships with different types of kindergartners (socially inhibited, hyperactive, and average) are related to their personal assessments of the severity and the causes of these children's behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…For example, children who feel well at school, compared to children who do not feel well at school, are more enthusiastic in participating at classroom activities, try harder, usually succeed, and, thus, become more confident about their school abilities (Ladd, Birch, & Bush, 1999;Mashburn, Hamre, Downer, & Pianta, 2006;Skinner, Wellborn, & Connell, 1990;Stephanou, 2005, submitted;Stipek, 1998). Also, positive emotions, such as curiosity, enjoyment, hope and pride, enhance motivation, facilitate learning and increase performance (Clore & Huntsinger, 2009;Meyer & Turner, 2002, Pekrun et al, 2002Stephanou, 2007Stephanou, , 2011b, whereas, intense negative emotions, such as anxiety, hopelessness, boredom and insecurity, and related thoughts, like a feeling of incompetent, interface with learning, decrease motivation, and is related to low performance (Kuyper, van der Werf, & Lubbers, 2000;Pekrun, 2005, Pekrun & Schutz, 2007Pekrun et al, 2010;Zeidner, 2007).…”
Section: Association Of Student Emotion With Their Competence Beliefsmentioning
confidence: 99%